Schedule randomization based countermeasures against timing attacks in real-time wireless networks - Samaddar, Ankita (Nanyang Technological University, 2022)
Cyber-physical systems are realized as those systems where the computation, communication and physical processes interact with each other (e.g., robotic systems, automotives, etc). A large class of cyber-physical systems are associated with strict timeliness requirements. They are known as ‘real-time systems’ (e.g., smart grids, avionics, etc).